The business survival of micro-enterprises in facing economic uncertainty - Mohamad Zaidi, Mohd Akmal Naim; Sapuan, Noraina Mazuin; Kusairi, Suhal (Penerbit Universiti Malaysia Pahang, 2022)
The current economic uncertainty, especially during the Covid-19 pandemic, has affected the global socio-economy. In Malaysia, to curb the spread of Covid-19 viruses, the government has implemented the Movement Control Order (MCO). This action has caused many SMEs (including micro-enterprises) not to be able to continue their operations as usual, mainly due to cash flow problems, operational instability and supply chain disruptions. Micro-enterprises are a significant contributor to local economic development. Hence, business continuity strategies are essential for these enterprises to continue and survive in the market. The government has introduced various methods to support these businesses. Meanwhile, virtuous strategic planning and management can improve the management's governance and integrity in making accurate decisions to achieve their goals. The implementation of digital marketing can upsurge the sale of micro-enterprises. This study intended to examine the relationship between government support, governance & strategic planning, operational restructuring and digital marketing with micro-enterprises business survival. This study uses a quantitative method with a total of 135 respondents among the owner of micro-enterprises in Complex Pekan Rabu, Kedah. Government support, governance & strategic planning and digital marketing were found to be survival determinants factors during the covid-19 pandemic.